1988
DOI: 10.1523/jneurosci.08-12-04427.1988
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of theophylline on spontaneous transmitter release from frog motor nerve terminals

SR Barry

Abstract: Alkylxanthine drugs, such as theophylline, block adenosine receptors, inhibit phosphodiesterases and other enzymes, and cause the release of calcium from intracellular stores. Adenosine receptor blockade occurs at low micromolar concentrations of the drugs, while other effects occur in the millimolar concentration range. The effects of theophylline were tested on spontaneous transmitter release at the frog cutaneous-pectoris neuromuscular junction (NMJ). A change in the frequency, but not the amplitude, of min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Firstly, selective A 2A or A 3 agonists and selective adenosine receptor antagonists were not examined in this study. Secondly, theophylline, used at high concentration (100 μM), is also a potent inhibitor of phosphodiesterases (Barry, 1988), and phosphodiesterase inhibition has been shown to increase IL-10 production (Mascali et al, 1996), thereby potentially masking its adenosine receptor antagonistic property. Thirdly, the adenosine uptake blocker dipyridamole was also incapable of preventing the stimulatory effect of adenosine on IL-10 production, secluding an intracellular, receptor-independent effect of adenosine.…”
Section: Adenosine Facilitates Il-10 Release By Monocytes and Macrophmentioning
confidence: 99%
“…Firstly, selective A 2A or A 3 agonists and selective adenosine receptor antagonists were not examined in this study. Secondly, theophylline, used at high concentration (100 μM), is also a potent inhibitor of phosphodiesterases (Barry, 1988), and phosphodiesterase inhibition has been shown to increase IL-10 production (Mascali et al, 1996), thereby potentially masking its adenosine receptor antagonistic property. Thirdly, the adenosine uptake blocker dipyridamole was also incapable of preventing the stimulatory effect of adenosine on IL-10 production, secluding an intracellular, receptor-independent effect of adenosine.…”
Section: Adenosine Facilitates Il-10 Release By Monocytes and Macrophmentioning
confidence: 99%
“…(Ribeiro & Sebastiao, 1987;Barry, 1988) but to a much smaller extent, in low [Ca2"]. (Bennett et al 1990).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, although it may be true that TMB‐8 was acting as an antagonist to both ryanodine and nicotinic receptors in our studies, there is no evidence suggesting that theophylline is altering transmitter release via the nicotinic receptors or that modest changes in ACh sensitivity will alter the effects of theophylline. The same can be argued for an affect on membrane conductance or protein kinase C activity because these are not relevant to the proposed sites of action of theophylline 20 . Furthermore, an earlier report demonstrated that TMB‐8 alone enhances transmitter release, 15 which is consistent with TMB‐8 antagonizing ryanodine receptors.…”
Section: Discussionmentioning
confidence: 96%
“…Theophylline and its derivative aminophylline have been used extensively to demonstrate the effects of cAMP on neurotransmission owing to their ability to inhibit cyclic nucleotide PDEs 2,5–9 . However, theophylline, in particular, has been shown to both enhance neurotransmitter release from vertebrate motoneurons 2,3 and inhibit transmitter release 15,20,21 . Aminophylline has also been shown to have varying effects on transmitter release 9 .…”
Section: Discussionmentioning
confidence: 99%